2001
DOI: 10.1021/jp004456e
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Scanning Optical Microscopy (NSOM) Studies of the Relationship between Interchain Interactions, Morphology, Photodamage, and Energy Transport in Conjugated Polymer Films

Abstract: It is becoming increasingly clear that the way in which a conjugated polymer film is cast affects the interactions between polymer chains and thus the optical and electrical properties of the film. Given that conjugated polymer films cast in different ways also show different nanometer-scale surface topographies, the question that arises is: What is the correlation between surface topography, local chain packing, and the local electronic properties of a conjugated polymer film? In this paper, we address this q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 49 publications
5
125
1
2
Order By: Relevance
“…We chose to study annealed MEH-PPV films because they contain a much higher degree of interchain interactions than as-cast films. 9,44 We find that even though the interfacial PL from annealed MEH-PPV films is spatially homogeneous in the absence of applied solvent, 44 the emission becomes spatially inhomogeneous in the presence of polar solvents. The data show that the majority of the detected interfacial emission from the annealed film shifts to the blue with increasing solvent polarity, indicating that most of the interchain species in the annealed film are excimer-like in nature, with an excited state that is less-polar than the ground state.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We chose to study annealed MEH-PPV films because they contain a much higher degree of interchain interactions than as-cast films. 9,44 We find that even though the interfacial PL from annealed MEH-PPV films is spatially homogeneous in the absence of applied solvent, 44 the emission becomes spatially inhomogeneous in the presence of polar solvents. The data show that the majority of the detected interfacial emission from the annealed film shifts to the blue with increasing solvent polarity, indicating that most of the interchain species in the annealed film are excimer-like in nature, with an excited state that is less-polar than the ground state.…”
Section: Introductionmentioning
confidence: 88%
“…This packing of the chains into low-energy structures also greatly increases the concentration of interchain species, as evidenced by a large redshift of the luminescence spectrum and a decrease of the PL quantum yield. 9,44 Our selection of annealed MEH-PPV films for this solvatochromism study provides two major advantages. First, the majority of the emission from annealed films is interchain, facilitating solvatochromic determination of the change in dipole associated with production of the interchain species.…”
Section: Solvatochromism Of Interchain Emission From Annealed Mementioning
confidence: 99%
“…Quanto maior o tamanho efetivo da conjugação, mais deslocados para valores menores de energias estarão os espectros eletrônicos de absorção e de emissão. O tamanho efetivo de conjugação é definido pelo valor médio de uma distribuição aleatória de segmentos com diferentes tamanhos de unidades adjacentes conjugadas 108,[111][112][113] . Esta distribuição estatística segue o modelo gaussiano e é conseqüência de defeitos na cadeia principal, gerados pela presença de ligações cis, de sítios oxidados, de grupos carbonila, de ligações alifáticas, ou por torções conformacionais geradas por influência de solventes, por pressão ou mesmo pela temperatura 114 .…”
Section: Propriedades Fotofísicas Dos Polímeros Eletroluminescentesunclassified
“…Efforts have been made to correlate PL and topography on the nanometer scale making use of near-field scanning optical microscopy (NSOM) and shear force microscopy. In thin films of MEH-PPV, Nguyen and coworkers 5 observed that topographic features (bumps) and local PL spectra were generally correlated for thin films of MEH-PPV which had been prepared from polymer dissolved in chlorobenzene (CB) and tetrahydrofuran (THF). A similar set of experiments performed by Huser and coworkers 6 with toluene as the solvent did not find any correlation between topography and PL intensity variations.…”
Section: Introductionmentioning
confidence: 99%